Konsep Poligami dalam Al-Qur’an (Studi Pemikiran Siti Musdah Mulia) - Faiz Romadhon, Febry; Muid N., Abd.; Nurbaiti, Nurbaiti (Journal of Comprehensive Science, 2025)
Polygamy in general is the practice of marriage where an individual has more than one partner at the same time and the current term polygamy is more identified with a husband who has more than one wife. This type of research is library research. The data sources used by the author are primary data related to the work of Siti Musdah Mulia and secondary data from various literature related to polygamy law. The research method used by the author is a descriptive-analytical method with a qualitative approach. The conclusion of this study shows that Siti Musdah Mulia rejects polygamy, considering it as a form of legalized infidelity and a violation of human values. He also expressed various negative impacts of the practice of polygamy, so that he expressly stated that polygamy is haram lighairih (haram because of the consequences). The various approaches used by Siti Musdah Mulia in interpreting the verses of polygamy are with a contextual approach, a justice approach, a maqâshid syarî'ah approach, a gender equality approach, and a holistic approach.